Description of Diduga siamensis sp. nov. and newly recorded D. scalprata (Lepidoptera, Erebidae, Arctiinae) from Thailand, with a checklist of the genus Diduga - Bayarsaikhan, Ulziijargal; Heppner, John B.; Kwon, Hyung Wook; Kim, Kil Won; Bae, Yang-Seop (Zootaxa, 2024)
In this study, 11 species of the genus Diduga Moore, [1887] are recognized from Thailand, including a new species, Diduga siamensis Bayarsaikhan & Heppner sp. nov., and one newly recorded species, D. scalprata Bayarsaikhan, Li & Bae, 2020. Illustrations of adults and genitalia of the additionally examined species are provided, with a checklist of known species of the genus from this country.